Improving the Storage Quality of Ready-to-Eat Clementine Fruits Using Lemon By-Products - Miriam Arianna Boninsegna; Alessandra De Bruno; Amalia Piscopo (Agriculture)
In this study, the effect of the antioxidant extract from lemon by-products (Citrus × Limon L.) integrated into an edible alginate-based coating was evaluated to preserve the storage quality of ready-to-eat Clementine (Citrus × Clementina) fruits. The effects of different coatings (1.5% of alginate and 1.5% of alginate + 2–4% of lemon by-product extract) were assessed by the physical, chemical, microbiological, sensorial, and structural analyses of ready-to-eat Clementine fruits stored for 21 d at 4 °C. Ready-to-eat Clementine fruits coated with alginate and extract from lemon by-products showed greater levels of polyphenols, flavonoids, antioxidant activity, and organic acids. A microbiological analysis revealed the dose-dependent effect of the extract to contrast the growth of mesophilic bacteria, yeast, and molds during storage. A sensory analysis confirmed that the enriched coating improved the visual, structural, and olfactory parameters until the end of storage. The evidence in this study proves that an antioxidant extract from lemon by-products is a great sustainable treatment to preserve ready-to-eat fruits.